Exploring the potential nutritional benefits of Arthrospira maxima and Chlorella vulgaris: A focus on vitamin B12, amino acids, and micronutrients - Durdakova, Michaela; Kolackova, Martina; Ridoskova, Andrea; Cernei, Natalia; Pavelicova, Kristyna; Urbis, Petr; Richtera, Lukáš; Pelcova, Pavlína; Adam, Vojtěch; Huska, Dalibor (Food chemistry, 2024)
Arthrospira (Limnospira) maxima (A. maxima) and Chlorella vulgaris (Ch. vulgaris) are among the approved microalgae and cyanobacteria (MaC) in the food industry that are known to be safe for consumption. However, both organisms are controversial regarding their vitamin B12 content, due to the possible occurrence of pseudo-cobalamin. Concurrently, their nutrition profiles remain understudied. The main purpose of the present study was to identify their nutrition profiles, focusing mainly on vitamin B12, amino acids, and micronutrients under iron-induced hormesis (10 mg/L Fe in treated samples). Our findings indicate a higher B12 content in A. maxima compared to Ch. vulgaris (both control and treated samples). Using liquid chromatography with tandem mass spectrometry (LC-MS/MS), the cyanocobalamin content was determined as 0.42 ± 0.09 μg/g dried weight (DW) in the A. maxima control and 0.55 ± 0.02 μg/g DW in treated A. maxima, resulting in an insignificant difference. In addition, the iron-enriched medium increased the amount of iron in both tested biomasses (p < 0.01). However, a more pronounced (approximately 100×) boost was observed in Ch. vulgaris, indicating a better absorption capacity (control Ch. vulgaris 0.16 ± 0.01 mg/g Fe, treated Ch. vulgaris 15.40 ± 0.34 mg/g Fe). Additionally, Ch. vulgaris also showed a higher micronutrient content. Using both tested microalgae, meeting the sufficient recommended daily mineral allowance for an adult is possible. By combining biomass from A. maxima and Ch. vulgaris in a ratio of 6:1, we can fulfill the recommended daily allowance of vitamin B12 and iron by consuming 6 tablets/6 g. Importantly, iron hormesis stimulated amino acid composition in both organisms. The profile of amino acids may suggest these biomasses as promising potential nutrition sources.
Keywords: Iron; Vitamin B 12; Cyanobacteria; tandemová hmotnostní spektrometrie; Amino Acids; Chlorella vulgaris; Micronutrients; Deficiency; Anemia; železo; Spirulina; Nutritive Value; Cobalamin; vitamin B 12; mikroživiny; mikrořasy; Microalgae; Amino acids; nutriční hodnota; Tandem Mass Spectrometry; aminokyseliny